2020
DOI: 10.1093/plphys/kiaa049
|View full text |Cite
|
Sign up to set email alerts
|

Distinct signaling routes mediate intercellular and intracellular rhizobial infection inLotus japonicus

Abstract: Rhizobial infection of legume roots during the development of nitrogen fixing root nodules can occur intracellularly, through plant-derived infection threads traversing cells, or intercellularly, via bacterial entry between epidermal plant cells. Although it is estimated that around 25% of all legume genera are intercellularly infected, the pathways and mechanisms supporting this process have remained virtually unexplored due to a lack of genetically amenable legumes that exhibit this form of infection. In thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 96 publications
1
57
0
Order By: Relevance
“…One of the intriguing questions regarding the infection of legume tissues by Rhizobium is the relationship between intercellular and intracellular modes of infection. An interesting model has recently been developed based on interaction of L. japonicus with different strains capable of infecting the host plant either via intracellular or via intercellular modes [ 281 ]. Furthermore, the presence of infection threads in root hairs during actinorhizal symbiosis [ 151 ] and the existence of common genes controlling Rhizobium infection and endomycorrhizal symbiosis [ 282 , 283 ] clearly indicate the early origin of infection threads during the course of the evolution of plants.…”
Section: Discussionmentioning
confidence: 99%
“…One of the intriguing questions regarding the infection of legume tissues by Rhizobium is the relationship between intercellular and intracellular modes of infection. An interesting model has recently been developed based on interaction of L. japonicus with different strains capable of infecting the host plant either via intracellular or via intercellular modes [ 281 ]. Furthermore, the presence of infection threads in root hairs during actinorhizal symbiosis [ 151 ] and the existence of common genes controlling Rhizobium infection and endomycorrhizal symbiosis [ 282 , 283 ] clearly indicate the early origin of infection threads during the course of the evolution of plants.…”
Section: Discussionmentioning
confidence: 99%
“…The infection process starts when rhizobia enter root systems through natural cracks between epidermal cells at the base of emerging lateral roots (termed “crack entry”), or, more commonly, when compatible rhizobia induce curling and deformation of growing root hairs around the bacterial cells that subsequently enter through an intracellular infection thread (IT, Figure 1A ; Rae et al, 2021 ). Crack entry infection is considered more primitive than ITs because the host does not experience sophisticated cellular differentiation of root hairs ( Sprent, 2008 ; Gage, 2019 ), although some species of plants (e.g., Lotus japonicus ) can alter their mode of infection depending on the site of infection ( Montiel et al, 2021 ). Only the emerging root hairs are infectable, with polar root hair growth required to achieve the necessary root hair deformation and cell wall invagination to form an IT ( Turgeon and Bauer, 1985 ; Esseling et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…These include Sesbania rostrata, where the infection mode can change in response to flooding (Herder et al 2006), and Lotus species, where intercellular infection appears to serve as a backup function to the preferred intracellular infection route through root hair infection threads. This phenomenon was observed in Lotus japonicus Gifu as rare infection events of spontaneous nodules in a NF receptor deficient genetic background (Madsen et al 2010) and has since been found in the L. japonicus Gifu interaction with IRBG74 (Montiel et al 2020) and in Lotus burttii interactions with Sinorhizobium fredii HH103 and Rhizobium leguminosarum Norway (Acosta-Jurado et al 2016b;Liang et al 2019). Generally, intracellular root hair infection appears to offer more stringent scrutiny of the rhizobial partner, whereas the compatibility requirements for intercellular crack entry appears to be more relaxed (Sprent 2007;Madsen et al 2010).…”
Section: Introductionmentioning
confidence: 87%
“…In Lotus, both inter-and intracellular infection depend on NF signalling (Acosta-Jurado et al 2016b;Montiel et al 2020), except in rare cases, if organogenesis is activated in the absence of Nod factor signalling (Madsen et al 2010). Candidate gene approaches relying on interspecific variation in Nod factor receptors has been used to demonstrate their roles in determining compatibility (Radutoiu et al 2007).…”
Section: Introductionmentioning
confidence: 99%